Pengelolaan Pembelajaran Dalam Proses Pengembangan Sosial Emosional Standar Pendidikan Anak Usia Dini - Siti Rosmayati; Arman Maulana; Sofyan Sauri; Ujang Cepi Barlian (Coopetition : Jurnal Ilmiah Manajemen, 2021)
In connection with descriptive data analysis, this research will describe from the results of documentation and field observations from the analysis of learning management in the process of social emotional development of PAUD Az-Zahra Islamic Preschool Cicalengka, Bandung Regency The results of the analysis documentation carried out by researchers on the management of learning in the process of social emotional development aged 4-5 years of 17 children at PAUD Az-Zahra Islamic Preschool Cicalengka, Bandung Regency. There are several indicators in learning management 1) Planning 2) Implementation of learning, namely activities before entering class, preliminary activities, core activities, eating and resting activities, closing activities 3) Evaluation, namely Assessment, Reporting and follow-up. So it can be concluded that the management of learning in the process of social emotional development of PAUD Az-Zahra Islamic Preschool Cicalengka Bandung Regency has been done by the teacher well according to the indicator although there are still two indicators that have not been implemented, the success of the teacher can be seen from the level of achievement of emotional social development a good boy.